Pengaruh Pendapatan Asli Daerah, Belanja Barang atau Jasa, dan Belanja Modal Terhadap Sisa Lebih Pembiayaan Anggaran pada Provinsi Bengkulu - M. Novan; Nelly Masnila; Nurhasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of regional original income (PAD), expenditure on goods/services, and capital expenditure on the budget surplus in the province of Bengkulu from 2017 to 2021. The population of this study includes 10 regencies/cities in the Bengkulu province. The research employed a saturated sampling method, resulting in 10 regencies/cities being selected as the research sample. The data used in this study were secondary data in the form of the Budget Realization Report of the provincial government in Bengkulu. Multiple regression analysis was used in this study, utilizing SPSS version 26 for data processing. The results of this study indicate that: (1) expenditure on goods/services has an influence on the budget surplus, while regional original income and capital expenditure do not affect the budget surplus. (2) Regional original income, expenditure on goods/services, and capital expenditure have an influence on the budget surplus.